Intraoperative Pulmonary Embolism during Nephrectomy for Renal Cell Carcinoma with Inferior Vena Cava Progress - EJIMA, Tadashi; KOTERA, Atsushi; NAKAYAMA, Yujiro; NARIMATSU, Noriko; HASHIMOTO, Masahiro; NONAKA, Takahiro (THE JOURNAL OF JAPAN SOCIETY FOR CLINICAL ANESTHESIA, 2012)
A 73-year-old man was scheduled for nephrectomy for left renal cell carcinoma with tumor thrombus in the inferior vena cava (IVC). During the surgery, a sudden decrease in SpO2, EtCO2 and BP occurred, and tumor thrombus in the IVC disappeared on the TEE image. Pulmonary embolism was suspected. As hemodynamic status was fairly stable, nephrectomy was performed. Computed tomogram after nephrectomy revealed an embolus in the right pulmonary artery. Immediate embolectomy was scheduled. Tumor embolus was successfully removed under cardiopulmonary bypass. Fortunately, tumor pulmonary embolism did not lead to cardiopulmonary collapse in this case. However, tumorembolism is sometimes fatal. We should have considered the placement of a temporary IVC filter before surgery to prevent it.